Chitosan nanoparticle loaded by epidermal growth factor as a potential protein carrier for wound healing: In vitro and in vivo studies - Samaneh Montazeri; Ali Rastegari; Zohreh Mohammadi; Mahboobeh Nazari; Maryam Yousefi; Fatemeh Yazdi Samadi; Somayeh Najafzadeh; Mehdi Aghsami (IET Nanobiotechnology)
Abstract Epidermal growth factor (EGF) can be efficiently used in wound healing process; but the main obstacle of its clinical use is its susceptibility to proteolysis and maintaining its effective concentration in the site of action. In this study, chitosan nanoparticles containing EGF is formulated using a simple method to increase its stability in physiological pH as well as protect its biological activity and effectiveness in wound healing process. Nanoparticles with different ratios of chitosan/EGF were prepared and evaluated in vitro and in vivo. Obtained results showed nanoparticles with 2:1 ratio of chitosan/EGF were able to release 80% of encapsulated protein after 12 h. Cell proliferation study demonstrated that prepared nanoparticles could protect EGF functionality in physiological pH. In vivo results showed that nanoparticles with 2:1 ratio of chitosan/EGF could significantly accelerate the wound closure‐rate, re‐epithelialisation and collagen deposition. In conclusion, the designed nanoparticles in optimal ratio can be considered as a potential vehicle for EGF delivery to wounds with the aim of improving healing process.